Influential Article Review - What Are the Information System Competencies That Managers Must Have? Advancement of Public Administration Degree Program - Townsend, Aleeza; Callahan, Dolcie; Coffey, Waqar (American Journal of Management, 2021)
This paper examines information technology. We present insights from a highly influential paper. Here are the highlights from this paper: This paper analyzes the competences required by executives to manage information system, and consequently, the competences that must define the information system subjects in non-technical degrees, degrees, such as Public Administration or Business Management. This work reviews the literature about business managers’ competences on Information Technologies (IT) and compares the theory with the traditional body of knowledge about information systems taught at business schools. By analyzing the executives’ function, their role in the information system management, and, above, all the importance of their decisions in the effective integration of IT in business processes, this work proposes specific development in seven knowledge areas that facilitate the acquisition of these types of executive competences. For our overseas readers, we then present the insights from this paper in Spanish, French, Portuguese, and German.